An adhesion code ensures robust pattern formation during tissue morphogenesis - Tony Tsai; Mateusz Sikora; Peng Xia; Tugba Colak-Champollion; Holger Knaut; Carl‐Philipp Heisenberg; Sean G. Megason (2020)
Convergence of paradigms yields patterns In embryo development, spatial patterns of distinct cell types arise reproducibly. In the zebrafish spinal cord, neural progenitors form stereotypic stripe patterns despite the noisy instructive signals and large-scale cellular rearrangement required during morphogenesis. Tsai et al. show that a cell type–specific adhesion code, regulated by a Shh morphogen gradient composed of three adhesion molecules, provides adhesion specificity for three neural progenitor types and mediates patterning robustness in the zebrafish spinal cord. Although insufficient on their own, the integration of the morphogen gradient and differential adhesion mechanisms enables robust pattern formation during tissue morphogenesis. Science , this issue p. 113